Wetted Front Advance under Point-Source Field Dripper System for Estimation of Unsaturated Hydraulic Conductivity Function - Derrick M. Denis and Sanjay Arora, Rohit Pratap Ojha*, Chhedi Lal Verma (Journal of the Indian Society of Soil Science, 2021)
Unsaturated soil hydraulic conductivity function is often required for designing a drip irrigation system. Point-source field dripper methods are available for quick measurement of saturated hydraulic conductivity (Ks) and scaling parameters of the soil. However, steady-state saturated front radii is difficult to differentiate compared to the wetted front radii, which is easy and precise. Field dripper methods were used for estimation of Ks and scale parameters using saturated front radii for four different soils viz., cultivated tilled and no-tilled normal and sodic soils. There exists a good consistency among the values obtained by using saturated as well as wetted front radii. Use of wetted front radii could be useful for measurement of Ks and scale parameter of the soil with more accuracy.